2020
DOI: 10.1021/acs.jpcb.0c07041
|View full text |Cite
|
Sign up to set email alerts
|

Lipase and Water in a Deep Eutectic Solvent: Molecular Dynamics and Experimental Studies of the Effects of Water-In-Deep Eutectic Solvents on Lipase Stability

Abstract: Given the accumulated evidence on the effects of water-in-deep eutectic solvents (DESs) on the solvent nanostructure and the yield of lipase reactions, here we have used molecular dynamics (MD) simulations to delineate the structure and dynamics of thermoalkalophilic lipases in choline chloride/urea-based DES (reline) with varying hydration levels. Results indicated that pure reline almost froze the lipase backbone, while hydrated reline that showed a less ordered nanostructure than the pure form introduced so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…At 10% of water content, the molecular flexibility of the enzyme increased which, in turn, can influence the enzymatic activity. At the same time, Shehata et al showed that slightly hydrated reline (5%) activates thermoalkalophilic lipases while the mobility of the lid domain that controls catalytic activity increases [283].…”
Section: Activity and Stability Of Enzymes In Des/water Mixturesmentioning
confidence: 99%
See 1 more Smart Citation
“…At 10% of water content, the molecular flexibility of the enzyme increased which, in turn, can influence the enzymatic activity. At the same time, Shehata et al showed that slightly hydrated reline (5%) activates thermoalkalophilic lipases while the mobility of the lid domain that controls catalytic activity increases [283].…”
Section: Activity and Stability Of Enzymes In Des/water Mixturesmentioning
confidence: 99%
“…DESs can be also used as a non-toxic and biodegradable reaction medium for redox biocatalysis [268]. The stability and activity of enzymes in DES with different water concentrations have been addressed using MD simulations [268,271,283]. Kumari et al [271] showed that the conformation of hen egg-white lysozyme is substantially destabilized in reline/water mixtures especially at 50/50 reline/water content.…”
Section: Activity and Stability Of Enzymes In Des/water Mixturesmentioning
confidence: 99%
“…DESs can be also used as a non-toxic and biodegradable reaction medium for redox biocatalysis [ 288 ]. The stability and activity of enzymes in DES with different water concentrations have been addressed using MD simulations [ 288 , 291 , 305 ]. Kumari et al [ 291 ] showed that the conformation of hen egg-white lysozyme is substantially destabilized in reline/water mixtures especially at 50:50 reline:water content.…”
Section: Main Directions Of Investigationsmentioning
confidence: 99%
“…In general, MD simulations lead to detailed atomistic insights into the enzyme behavior in a specific reaction medium and can unravel structural changes and the interactions between enzyme and solvents, which can then be correlated experimentally. MD simulations have mainly been utilized to study lipases in organic solvents and DESs, 13,[37][38][39] but recently also other enzymes gained attention for studying their behavior in different solvents with molecular methods. 40,41 Importantly, the underlying models of MD simulations are interaction models (the so-called force field).…”
Section: Introductionmentioning
confidence: 99%
“…In general, MD simulations lead to detailed atomistic insights into the enzyme behavior in a specific reaction medium and can unravel structural changes and the interactions between the enzyme and solvents, which can then be correlated experimentally. MD simulations have mainly been utilized to study lipases in organic solvents and DESs, 13,[37][38][39] but recently other enzymes have also gained attention for studying their behavior in different solvents with molecular Scheme 1 Illustration of the distribution of water around an enzyme in a non-aqueous solvent. The space around the enzyme can be distributed into two different regions: (1) a protein vicinity region, where the interaction of water with the protein (here shown horse-liver alcohol dehydrogenase, HLADH) dominates, and (2) a bulk phase, where the interaction of water with the solvent mixture is dominant.…”
Section: Introductionmentioning
confidence: 99%